Pizza Kacang Hijau Sebagai Intervensi Diet Untuk Anak Autisme Dan Attention Deficit Hyperactivity Disorder (ADHD - Fitriyani, Vika Ramadhana; Lababah, Ainiyatul luklukatul; Zakiyah, Zakiyah; Ananditha, Aries Chandra (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
Objective: Autism and ADHD children were special need child that have to need their own diets. For autism gluten and casein patients are considered toxic, because the body with autism does not produce enzymes digest gluten. As a result, these undigested proteins are converted into chemical components called opoids. Opoid itself, like drugs such as opium, morphine, and heroin that works as toxins that can interfere with brain function and immune system, causing behavioral disorders. for this study aimed to describe the effect of green bean pizza for diet in children with autism and ADHD.Methods: The method used in this research is case study. The population studied were children with autism and ADHD. Cases used are children with autism. Data collection was done by observation to the respondent before and after givenGreen Peanut Pizza. Univariate data analysis technique using quantitative.Results: In the observation of hyperactive activity of children before and after intervention for 1 week showed improvement. The child's previous hyperactive level is often (almost daily) less frequent (approximately once a week). The child's mother reports that the child is only doing aggressive behavior while facing a situation that really makes his feeling emotionally.Conclusion: Green Bean Pizza is an alternative solution for children's diets with autism and ADHD as it proves to decrease the rate of hyperactivity in children with autism and ADHD.